EFFECT OF SALACIA OBLONGA ROOT EXTRACT AGAINST CLINICAL ISOLATES STAPHYLOCOCCUS AUREUS - ANANTHULA MOUNIKA; BHARGAVI POKALA; MD., ZAHOORULLAH S; ANJANEYULU MUSINI (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: Salacia oblonga Wall. is an important medicinal plant belonging to the family Celastraceae. The study reports the effect of S. oblonga root extracts against clinical isolate Staphylococcus aureus Methods: Antibacterial activity was evaluated by agar diffusion method and assay for minimum inhibitory concentration (MIC) of extract. Further, the effect of S. oblonga extract determined by DNA fragmentation and respiratory dehydrogenase enzyme activity assays. Results: S. oblonga ethyl acetate root extract was evaluated for antibacterial activity towards clinical isolate S. aureus. Bacterial growth was determined in treated and control cells. Extract displayed good growth inhibition and MIC of the extract was 80 μg/ml. DNA fragmentation assay was carried out, this result has shown that treated bacterial cell has DNA damage compared to the control cell. Further, respiratory dehydrogenase enzyme activity was determined. In the treated cells, enzyme activity was low compared to the control cells. Conclusion: Salacia oblonga root extract inhibiting the growth of S. aureus by different modes of action.